2019
DOI: 10.4012/dmj.2019-021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the resin infiltration and CPP-ACP applications before orthodontic brackets bonding

Abstract: The aim of this study is to investigate the efficiency of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) gel and resin infiltrant on decalcified enamel, and to explain the correlation, if any, between ion release capacities and shear bond strength (SBS). A total of 80 premolar teeth were used (n=20). Group I was the control, while a demineralization protocol was performed for other groups. CPP-ACP gel and resin infiltrant, respectively, was applied to Groups III and IV. Pre and post-demineralizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 28 publications
2
18
1
1
Order By: Relevance
“…In this systematic review, twenty-three articles reported information about microhardness , ten evaluated surface roughness, [27,31,37,47,[49][50][51][52][53][54], sixteen assessed the penetration depth [40,46,50,[55][56][57][58][59][60][61][62][63][64][65][66][67] and eight explored shear bond strength after resin infiltration [32,52,[68][69][70][71][72][73].…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this systematic review, twenty-three articles reported information about microhardness , ten evaluated surface roughness, [27,31,37,47,[49][50][51][52][53][54], sixteen assessed the penetration depth [40,46,50,[55][56][57][58][59][60][61][62][63][64][65][66][67] and eight explored shear bond strength after resin infiltration [32,52,[68][69][70][71][72][73].…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Overall, twelve studies included bovine teeth (n per group = 803) while twenty-five studies included human teeth (n per group = 865). Nine studies reported data without specimen demineralization previously to resin infiltration [47,54,55,57,59,[61][62][63][64]74] and thirty-nine articles included the demineralization process before the infiltrative resin [21,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][48][49][50][51][52][53]56,58,60,[65][66][67][69][70][71][72][73]. The demineralization process consists of emerging the teeth in a demineralization solution, with pH between 4 and 5 for a period of time that ranges from 1 min to 1200 h, to simulate the formation of WSLs (Table…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…In this study, higher SBS values were obtained in the intact enamel group than in the demineralized enamel group, in accordance with previous studies, but the difference was not statistically significant. However, Gulec and Goymen also found no statistically significant difference between the SBS values of brackets placed on the intact enamel surface and the demineralized enamel surface (32). One reason for these different results may be that different demineralization protocols were applied.…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with previous studies (28,31,35), our study found that the use of ICON and CPP-ACP on the demineralized enamel surface increased the SBS strength of the brackets, but there was no statistically significant difference when these two groups were compared with the intact enamel surface and demineralized enamel surface groups. Gulec and Goymen found that ICON and CPP-ACP applied to the demineralized enamel surface had brackets with SBS values lower than those on the intact enamel surface and those directly adhered to the demineralized enamel surface (32). Some reasons for this difference may include the application time of the pretreatment agents, the different waiting times in the artificial saliva solution, the use of thermal cycles and the development of bonding agents or bracket retention properties.…”
Section: Idr -Volume 11 Number 2 2021mentioning
confidence: 99%
“…The protective effect of resin infiltrant on sound tooth enamel provides a new attempt on prevention of dental caries, which may be used in preventing dental caries in people at high caries risk, such as patients who will undergo orthodontic treatment. According to reports, the incidence of white spot lesions in patients who have not undergone orthodontic treatment is between 11–24% ( Gulec & Goymen, 2019 ). The prevalence of white spot lesions after treatment fixed orthodontic appliances is 23%, 50% or even 97% ( Kobbe et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%